Manifestations of Paradox in the Poetry of Duraid ibn al-Simma al-Jashmi - Jaber Khamis Abbas, Assistant Professor Dr. (lark, 2026)
Paradox has become a central focus in modern literary and critical studies, as writers and poets use it to express ideas in an artistic and aesthetic manner. Beyond its rhetorical function, paradox operates as a key literary device, revealing contradictions between appearance and reality, or between expression and intended meaning. It deepens interpretation, stimulates reflection, and engages readers in constructing meaning by highlighting inherent tensions within the text. Paradox also enhances the poetic quality of literature through its conciseness and density. This study shows that paradox is a vital element in Duraid ibn al-Simma’s poetry, structuring his work around opposition and semantic tension. It enriches meaning and encourages readers to move beyond surface interpretations toward deeper contemplation. Furthermore, the conditions of pre-Islamic Arab life, including wars, conflicts, and raids, shaped this expressive technique, making paradox an effective tool for conveying the poet’s lived experience and his response to the challenges and uncertainties of life.